Sickle cell disease and Bartonella spp. infection - Paulo Eduardo Neves Ferreira Velho; Marna Elise Ericson; David Mair; Kalpna Gupta (Mediterranean Journal of Hematology and Infectious Diseases)
Sickle cell disease is the most common hereditary hematologic disorder in the world. Painful vaso-occlusive crises are the hallmark of the disease and it is difficult to treat. Chronic infection is related to a higher painful crisis rate in these patients. Bartonella spp. are fastidious bacteria of zoonotic transmission. They can cause human asymptomatic infection as well as fatal outcome. Pain, fatigue and fever, characteristic features of Bartonella spp. infection are manifest in sickle cell disease patients. Bartonella spp. infection should be ruled in sickle cell disease patients.